Analysis of porosity comparison formed on film layer of self-processed copal and alcohol based varnish against manufacture based varnish - Dewi, Agustina; Hasratiningsih, Zulia; Karlina, Elin; Greviana, Nadia (Universitas Padjadjaran, 2016)
Introduction: Varnish is one of the dental materials that can be used to protect the pulp. Raw materials for making varnish were easy to be obtained using simple technique and composition. Self-processed varnish which has 40 gr of copal, 50 ml of 95% alcohol and 10 ml of chloroform was produced. When applied, varnish formed a thin film layer which tend to porous. The purpose of this study was to analyze the comparison between porosity which formed in film layer of self-processed and factory varnish. Method: This study was true experimental with 12 third upper molars that had been cut horizontally as specimens and were divided into 2 groups as treated and control groups. First group had 1, 2, 3 and 4 times application of processed varnish as treated sample and second group samples were applied with factory varnish as control sample. Porosity was tested using SEM then its percentage was calculated by comparing the porosity and the tooth area. The data was then tested with t- independent test. Result: The result showed that self-processed varnish obtained larger percentage of porosity. Started at the third application time, both processed and factory varnish showed no porosity. Conclusion: The conclusion of this study was that there is difference between porosity which formed in film layer of self-processed and factory varnish.